Circulating activated innate lymphoid cells and mucosal-associated invariant T cells are associated with airflow limitation in patients with asthma - Ishimori, Ayako; Harada, Norihiro; Chiba, Asako; Harada, Sonoko; Matsuno, Kei; Makino, Fumihiko; Ito, Jun; Ohta, Shoichiro; Ono, Junya; Atsuta, Ryo; Izuhara, Kenji; Takahashi, Kazuhisa; et al. (Allergology international, 2017)
A variety of innate subsets of lymphoid cells such as natural killer (NK) cells, several populations of innate lymphoid cells (ILCs), and mucosal-associated invariant T (MAIT) cells as innate-like T lymphocytes are involved in asthma and may have important effector functions in asthmatic immune responses. In the present study, we investigated whether NK cells, ILCs, and MAIT cells in the peripheral blood of patients with asthma would be associated with clinical asthma parameters. We recruited 75 adult patients with mild to severe asthma. The peripheral blood mononuclear cells in peripheral venous blood samples from the patients were purified and stained with different combinations of appropriate antibodies. The cells were analyzed by flow cytometry. The percentage of activated (i.e., CD69+) NK cells in the total NK cell population was negatively correlated with FEV1% which is calculated by the forced expiratory volume in 1 s (FEV1)/the forced vital capacity (FVC). The percentages of CD69+ ILC1s and ILC2s were negatively correlated with FEV1% and %FEV1. The percentage of CD69+ ILC3s was positively correlated with BMI, and the percentage of CD69+ MAIT cells was negatively correlated with FEV1%. Moreover, the percentage of CD69+ NK cells, ILC1s, ILC2s, ILC3s, and MAIT cells were positively correlated with each other. For the first time, our data showed that activated NK cells, ILC1s, ILC2s, ILC3s, and MAIT cells were positively correlated with each other and may be associated with airflow limitation in patients with asthma. [Display omitted]